Sliding sector–based adaptive controller for seismic control of structures equipped with active tuned mass damper. (May 2023) - Saadatfar, Saman; Emami, Fereshteh; Khatibinia, Mohsen; Eliasi, Hussein
Abstract: Active tuned mass damper (ATMD) as a reliable active device of structural control can protect structures subjected to earthquake excitations from the severe seismic damages. The present study focus on the design of an adaptive sliding sector controller (ASSC) employed in the ATMD system to mitigate the seismic responses of an 11–story shear building under earthquake excitations. The ASSC technique is designed based on the hyper-surface of the sliding mode which is surrounded by a sector and can consider the uncertainty of system parameters. In this study, the design of the ASSC strategy is first implemented for the structure subjected to an artificial earthquake excitation. Then, the performance of the ASSC strategy is evaluated in mitigating the seismic responses of the structure under four near– and far–fault earthquake excitations. Furthermore, the efficiency of the ASSC strategy is also compared against that of a few control techniques including proportional-integral-derivative [PID], linear-quadratic regulator [LQR], fuzzy logic control [FLC], optimal sliding mode control [OMSC]. Comparative results of the numerical simulation confirm the robustness and ability of the ASSC strategy for the reduction of the structural responses under real earthquake excitations.